The influence of product packaging on consumer final choice - Pliasetska, V. R. (ТДАТУ, 2019)
The purpose of this article is to study the influence of packaging on the final choice of the consumer, as well as to consider the problems associated with recycling, communication with customers and the effect of color on them.
Keywords: product packaging; the influence of packaging; the choice of products